Industrial Automation and Robotics - Westcott, Jean (Mercury Learning and Information, 2023)
The updated edition of this book presents an introduction to the multidisciplinary field of automation and robotics for industrial applications. The book initially covers the important concepts of hydraulics and pneumatics and how they are used for automation in an industrial setting. It then moves to a discussion of circuits and using them in hydraulic, pneumatic, and fluidic design. The latter part of the book deals with electric and electronic controls in automation and final chapters are devoted to robotics, robotic programming, and applications of robotics in industry. New chapters on UAVs (Ch. 19) and AI in Industrial Automation (Ch. 20) are featured. The companion files include numerous video tutorial projects.